﻿The effectiveness of the use of polypeptide drugs and their effect on the metabolic parameters of oral fluid in patients with generalized periodontitis in depending on blood type - Yurii Bandrivsky; Orysia Bandrivska; Nataliia Malko; Larysa Posolenyk; Oksana Vydoinyk; Maryana Iskiv (Pensoft Publishers, 2022)
The article presents the results of treatment of 157 patients with generalized periodontitis depending on blood type using polypeptide drugs. The concentration of total protein, C - reactive protein, IgG, TRACP, BSALP, albumin, amylase, lipase, Ca, Fe was determined in the oral fluid. The treatment allowed to reduce the content of total protein, C - reactive protein, TRACP in the oral fluid with increasing levels of calcium, Fe, BSALP, in relation to the relevant data before treatment. And also, polypeptide drugs helped to increase the level of albumin in representatives of 0 (I) and A (II) blood type in the oral fluid; contributed to a decrease: glucose, IgG with increasing activity, amylase and lipase in carriers of B (III) and AB (IV) blood type in the oral fluid, in relation to the values before treatment. The dynamics of indicators of oral fluid metabolism with the help of polypeptide drugs, convincingly proves the effectiveness of their use in the treatment of generalized periodontitis in patients with different blood type.